Smoking Cessation Practices of Rural and Urban Health Care Providers - Linda D. Scott; Kathleen B. LaSala; Carolyn Z. Lyndaker; Sherry Neil-Urban (Rural Nurse Organization; Binghamton University, 2003)
The purpose of this descriptive research was to identify the similarities and differences of demographic characteristics, specific intervention practices, perceived barriers, and enhancement factors associated with smoking cessation interventions of rural and urban primary health care providers. A convenience sample consisted of 342 physicians, registered nurses, and advanced practice nurses with the majority of urban health care providers being younger aged physicians and advanced practice nurses compared to older, registered nurses in rural areas. Findings revealed minimal basic educational preparation of health care providers for smoking cessation interventions. Rural health care providers reported diverse, multiple practice settings with a generalist view, estimated that more of their clients smoked, and were less likely to assess clients' smoking practices and initiate smoking interventions. Consistent, strong curricula education at all health provider levels and continuing education for new and more effective strategies is essential to empower health care providers to address smoking cessation interventions consistently and effectively. Keywords: Smoking Cessation, Enhancement Factors, Barriers, Interventions, Rural Health Care Providers, Urban Health Care Providers